A vote of confidence : a novel - Hatcher, Robin Lee (Hatcher, Robin Lee. Sisters of Bethlehem Springs., 2009)
Beautiful and single Guinevere Arlington knows her "place" in the early 20th century. She just refuses to stay there. As she runs for mayor--and falls in love with her opponent--Gwen realizes winning may come at too high a price.